1991
DOI: 10.1111/j.1440-1681.1991.tb01427.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cyclic GMP Phosphodiesterase by Xanthine Derivatives Relaxes Guinea‐pig Trachealis Smooth Muscle

Abstract: 1. For the purpose of clarifying the mechanism of the airways smooth muscle relaxant action of xanthines, cyclic guanosine monophosphate (GMP) phosphodiesterase (PDE) from guinea-pig trachealis muscle was purified with diethylaminoethyl ether (DEAE) cellulose column chromatography. 2. Five 3-alkylxanthines (3-methylxanthine, 3-ethylxanthine, 3-n-propylxanthine (enprofylline), 3-n-butylxanthine, and 3-iso-butylxanthine), and five 1-methyl-3-alkylxanthines (1-methyl-3-methyl-xanthine (theophylline), 1-methyl-3-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…Adenosine antagonism may account for this effect, as xanthines are known to act as competitive antagonists at adenosine receptors and there is evidence to suggest that this mechanism underlies their relaxing effects. In accordance, 3-MX was found to be less potent than theophylline in both relaxing the guinea pig tracheal smooth muscle and elevating the concentration of cyclic nucleotides [24,25]. In the same line, 8-p-sulphophenyltheophylline (8-PT), a xanthine analogue, was shown to block the purinergic-receptormediated enhancement of electrical field stimulation in the rabbit bronchial smooth muscle [41].…”
Section: Relaxing Effects Of 1-mx and 3-mx And Speculations For The Umentioning
confidence: 74%
See 2 more Smart Citations
“…Adenosine antagonism may account for this effect, as xanthines are known to act as competitive antagonists at adenosine receptors and there is evidence to suggest that this mechanism underlies their relaxing effects. In accordance, 3-MX was found to be less potent than theophylline in both relaxing the guinea pig tracheal smooth muscle and elevating the concentration of cyclic nucleotides [24,25]. In the same line, 8-p-sulphophenyltheophylline (8-PT), a xanthine analogue, was shown to block the purinergic-receptormediated enhancement of electrical field stimulation in the rabbit bronchial smooth muscle [41].…”
Section: Relaxing Effects Of 1-mx and 3-mx And Speculations For The Umentioning
confidence: 74%
“…However, apart from the recently shown effects on the rabbit small intestine and ascending colon [26], information about the actions of theophylline's metabolites is strictly confined to airway tissues. Thus, 3-MX was documented to relax the human, cat and guinea pig airways [21,24,25], while 1-MX has been shown to relax in vitro dog and guinea pig airway smooth muscles [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 1996) and in rats (Ramzan & Levy, 1986), as well as to the relaxing activity of 3‐MX on the human, cat and guinea‐pig airways (Persson & Andersson, 1977; Ogawa et al. , 1989; Tanaka et al. , 1991).…”
Section: Introductionmentioning
confidence: 82%
“…Tanaka et al [7] reported that the tracheal relaxant effect of xanthine derivatives is closely related both to their cAMP and their cGMP PDE inhibitory effecs. It has been reported that PDE enzyme activity may be altered in diseases such as diabetes mellitus, hypertension, hyperthyroidism and hypothyroidism [8,9].…”
Section: Discussionmentioning
confidence: 99%